Birds of Central America : Belize, Guatemala, Honduras, El Salvador, Nicaragua, Costa Rica, and Panama - Vallely, A. C. (Andrew C.); Dyer, Dale (Artist) (Princeton field guides., 2018)
The first comprehensive field guide to the birds of Central AmericaBirds of Central America is the first comprehensive field guide to the avifauna of the entire region, including Belize, Guatemala, Honduras, El Salvador, Nicaragua, Costa Rica, and Panama. Handy and compact, the book presents text and illustrations for nearly 1,200 resident and migrant species, and information on all rare vagrants. Two hundred sixty detailed plates on convenient facing-page spreads depict differing ages and sexes for each species, with a special focus on geographic variation. The guide also contains up-to-date range maps and concise notes on distribution, habitat, behavior, and voice. An introduction provides a brief overview of the region's landscape, climate, and biogeography. The culmination of more than a decade of research and field experience, Birds of Central America is an indispensable resource for all those interested in the bird life of this part of the world. Detailed information on the entire avifauna of Central America260 beautiful color platesRange maps, text, and illustrations presented on convenient facing-page spreadsUp-to-date notes on distribution supported by an extensive bibliographySpecial focus on geographic variation of bird species.